Stimuli-responsive plasmonic core-satellite assembly with DNA linkers for ATP sensing - Liu, Xiaohui (2015)
Nanotechnology, a relatively new discipline, has been developed to promote the well-being of mankind, especially in the biomedical field. Specifically,biosensors designed with gold nanoparticles (AuNPs) have been widely used to detect various substances such as DNA. This paper describes the core-satellite nanostructures (CSNSs) as biosensors. They are assembled with binary AuNPs (14 nm AuNPs and 50 nm AuNPs), which is bridged by DNA linkers. The current key finding of the nanostructure is that it can be treated as a colorimetric reporter to indicate PH changes in-vitro and in live cells. On the basis of this finding, experiments were conducted to study its feasibility to monitor ATP changes in-vitro. In this paper, the synthesis of 14 nm AuNPs and 50 nm AuNPs will be described in detail. What’s more, the development of the core-satellite assembly will also be illustrated. Finally, figures as well as statistics will be analyzed to support our finding. This study prove that DNA linker bridged core-satellite assembly of binary AuNPs offers the possibility for us to detect ATP changes by plasmonic imaging in-vitro.